Threats and Conservation Problems of Non-Human Primates in Moist Deciduous Forest of Bangladesh - Naher, Habibon; Khan, Shawkat Imam; Ahmed, Tanvir (Journal of the Asiatic Society of Bangladesh, Science, 2017)
A study was conducted at the Madhupur deciduous forest, Tangail from April 2015 to October 2015. It was carried out. Formal and informal questionnaire survey was used to interview the forest staffs and local people of the peripheral villages of Madhupur forest. Habitat destruction due to expansion of agricultural land and illegal logging and firewood collection was the prime threats of primates’ conservation especially Langur endurance. Hunting by ethnic people for using food was another threat for primates’ survival. Diseases and road accident were additional cause of threats. Crop raid was the main factor for human primates’ conflict. Paddy, pineapple and jackfruits were severely damaged by primates as they spoiled more crops than they actually eat. Time and economic loss was due to engagement of people guarding the crop field till harvesting. Asiat. Soc. Bangladesh, Sci. 43(1): 11-22, June 2017